ЭЛЕКТРОТЕХНИКА, РАДИОТЕХНИКА ВА ЭЛЕКТРОНИКА ФАНИНИ ЎЗЛАШТИРИШДА ТАЛАБАЛАР МУСТАҚИЛ ИШЛАРИНИНГ ТАКОМИЛЛАШТИРИЛГАН МАЗМУНИ - Орынбетов, Нурылла (SCIENCE and SOCIETY, 2018)
Creating a self-help system in the article, we proposed ways in which students can independently achieve certain results. As a result, students' thinking will be improved. At the same time, they have more independent thinking, more creativity in learning activity.
Keywords: i